Standardization of Factor VIII – III. Establishment of a Stable Reference Plasma for Factor VIII-Related Activities - Barrowcliffe, T W; Tydeman, M S; Kirkwood, T B L; Thomas, D P (Thrombosis and Haemostasis, 1983)
An international collaborative study has been carried out to establish a reference plasma for Factor VIII-related activities. The freeze-dried reference plasma, coded 80/511, was assayed against fresh normal plasma, local standards and another freeze- dried plasma. There was good agreement between laboratories for the comparison of the two freeze-dried plasmas, but wide variation in the comparison of plasma 80/511 with fresh normal plasma and local standards, indicating the differences in Factor VIII content of local pooled plasmas. There were no significant differences between the one-stage and two-stage assays of VIII :C, or between electroimmunoassay (EIA) and immuno- radiometric (IRMA) assays of VIII R:Ag. However, in VIII R: RCoF (ristocetin co-factor) assays, the aggregometry methods gave lower values than the macroscopic and counting methods for the comparison of freeze-dried against fresh normal plasmas. From the combined results of assays against each laboratory’s fresh normal plasma, potencies were assigned to plasma 80/511.Results from accelerated degradation studies indicated that losses of each VIII-related activity in plasma 80/511, when stored at -20° C, should be less than 0.01% per year, indicating its suitability to serve as a long-term reference preparation. Plasma 80/511 has been established by the WHO Expert Committee on Biological Standardization as the 1st International Reference Preparation for Factor VIII-Related Activities in Plasma.
Keywords: Factor VIII; Plasma; Reference preparation